64 Biomarker-based index for detecting sarcopenia in patients with cardiovascular disease. (13th January 2020) - Kai, H; Harada, H; Niiyama, N; Katoh, A
Abstract: Background: Clinical significance of sarcopenia has been highlighted in patients with cardiovascular disease (CVD). Sarcopenia is generally diagnosed based on the decrease in skeletal muscle index (SMI) and the reduction of either handgrip strength or gait speed. However, SMI is difficult to measure for general physicians or cardiologists, because special, expensive equipment (i.e. bioelectrical impedance assay (BIA) or dual-energy X-ray absorptiometry) is necessary. Purpose: The aim of this study was to seek a new, simple index to detect sarcopenia in CVD patients. Methods: We retrospectively investigated the association of sarcopenia with physical examination data and circulating biomarkers of nutrition, inflammation, skeletal muscle homeostasis in 132 CVD patients who admitted in our hospital. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia (AWGS) guidelines using SMI measurements by BIA method. Results: Among the screened biomarkers (e.g. hsCRP and IL-6), serum adiponectin and sialic acid was significantly higher in sarcopenic patients (n = 39) than non-sarcopenic patients (n = 93). On stepwise multivariate regression analysis, adiponectin, sialic acid, sex, age, and body mass index were independent detecting factors for sarcopenia based on AWGS criteria. ROC curve analysis revealed high accuracy for sarcopenia detection of the biomarker-based sarcopenia index (BMI), obtained from the regression formula using the independent factors (Figure). Conclusions: Novel biomarker-based sarcopenia index would be a simple, useful tool for detecting sarcopenia in CVD patients.